Potensi Madu sebagai Penurun Tekanan Darah dan Kolestrol - Mitha Fransiska; Jaka Fadraersada; Fajar Prasetya (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2019)
Hypertension is an increase in systolic and diastolic blood pressure more than 140/90 mmHg. Honey has the potential to reduce blood pressure because it has 200 chemical substances. This study aims to ford the effectiveness of giving honey to reduce blood pressure and cholesterol levels in hypertensive patients, as well as knowing the content of secondary metabolites found in honey. The research method used was semi quantitative with pre and post procedurs. Honey contains secondary metabolites of alkaloids, flavonoids, tannins, and saponins. The results of the analysis of honey give a significant decrease in systolic pressure, diastole, heart rate and cholesterol levels. Consumption honey regularly effectively reduces blood pressure in hypertensive patients.